Worthy Brown's daughter - Margolin, Phillip (Harper, 2014)
One of a handful of lawyers in the new state of Oregon, recently widowed Matthew Penny agrees to help Worthy Brown, a newly freed slave, rescue his fifteen year old daughter, Roxanne, from their former master, a powerful Portland lawyer. Worthy's lawsuit sets in motion events that lead to Worthy's arrest for murder and create an agonizing moral dilemma that could send either Worthy or Matthew to the hangman.